PEMILU BERINTEGRITAS (STUDI PENDAFTARAN PEMILIH TERHADAP PENGGUNA SURAT KETERANGAN DOMISILI DALAM PILKADA SAMOSIR TAHUN 2015) - Tota Pasaribu; R. Widya Setiabudi Sumadinata; Muradi Muradi (Journal of Governance, 2018)
This study analyzes about accomodating the electors registration for those Who do not have citizenship document. Due to the equality guarantee of Political rights and universal suffrage to each citizen is a format of democratic and integrated election without any discrimination. The problem arise is how effective the presence of domicile certificate in protecting the citizen suffrage is? Analizing it by using qualitative approach of case study. The result shows that 1,36% or 1.285 People of 94.454 total of their voter list are novice voter, apathetic voters to their demographic documents and voters from trusts who previously had Lost the election rights. However the polemic emerged later is even stipulated in the regulation of general election commission, it is feared to result in mibilization as well as in contrast with domicile administrative formation. Hence, for the election data accuracy, regulation adjustment is needed between voter data and population, maintaining sustainable previous voter data base Key Word: Integrated Election, Voter Registration, SKD, KPU Samosir.